Pelatihan Penelitian Tindakan Kelas untuk Meningkatkan Karier Guru - Ulfa, Maria; Ningrum, Ayu Setya; Septiani, Dini; Astuti, Melyana Puji; Utami, Fitria Dwi (LPPM Universitas Flores, 2023)
Professional teachers don't just spend all their time teaching. But through teaching activities, the teacher can make research that can be used as career advancement. The research is in the form of Classroom Action Research or CAR. By making CAR the teacher can carry out the process of analyzing the difficulties in the learning process faced by students. CAR is the process of teaching teachers, then analyzing the results of the learning process, finding solutions to the results of the learning process, implementing solutions, and increasing the quality of learning. CAR is something that must be done every day by the teacher. Through Community Service (PKM) activities with the theme Classroom Action Research Report Preparation Workshop made by students and lecturers of PGSD Study Program, STKIP Kusuma Negara to teachers in Indonesia which were held Thursday to Tuesday, 09 to 12 January 2023, it is hoped that this will help participants in making and compiling CAR reports to enhance teacher careers